The Effect of Preheating Using Microwave, Steam, and Oven on the Quality of Ponorogo Chicken Satay (Jurnal Ilmu dan Teknologi Hasil Ternak, 2022)
This study aims to determine the effect of different preheating methods on the quality of Ponorogo chicken satay. The study used a Nested Completely Randomized Design. The preheating methods used include microwave, steam, and oven with a preheating time of 5 and 10 minutes. The parameters used are physical quality (pH, WHC and cooking loss), chemical quality (moisture, protein and fat content), and Polycyclic aromatic hydrocarbons (PAHs). Data were analyzed using Analysis of Variance (ANOVA), if the results of the analysis obtained data that were significantly different or very significant, it would be continued with Duncan's Multiple Range Test (UJBD) and PAHs analysis of descriptively. The results of statistical analysis showed that the use of different preheating methods had a very significant effect (P<0.01) on pH and fat content had a significant effect (P<0.05) but had no significant effect (P>0.05) on Water Holding Capacity (WHC), cooking loss, moisture and protein content. The duration of preheating in heating method had a significant effect (P<0.05) on WHC and moisture content, but it had no significant effect (P>0.05) on pH, cooking loss, protein and fat content. PAHs content of Ponorogo chicken satay with long heating using microwave (23.35 mg/kg and 5.99 mg/kg), steam (5.48 mg/kg and not detected), oven (8.22 mg/kg and 7.31 mg/kg). The conclusion of this study that the use of preheating method with a long time can reduce the content of Polycyclic aromatic hydrocarbons (PAHs), physical, chemical, organoleptic quality and the best model is obtained in the steam method with a temperature of 97Â°C.